Fatigue analysis of dental prostheses by finite element method (FEM) - Hernandez, Bruno Agostinho [UNESP]; Paterno, Alexander [UNESP]; Sousa, Edson Antonio Capello [UNESP]; De Oliveira Freitas, João Paulo [UNESP]; Foschini, Cesar Renato [UNESP] (ASME International, 2015)
Introduction and Objectives: The dental prostheses are typical biomechanical structures because they have the objective to restore the mastication functions and are responsible for replacing the original tooth that was damaged. In the last few years, many studies have been done and big achievements have been noticed in this area. However, clinical studies and experimental procedures for these conditions are sometimes impractical, due to the biological nature of these components and the difficult to reproduce and to analyze such conditions. Moreover, it involves complex geometries, loads and mechanical behaviors, which analytical solution is very difficult to achieve. For these reasons, many researchers have applied the Finite Element Method (FEM). This method allows the evaluation of non-linear situations (e.g. biomechanical interactions) with complex geometries where experimental tests are usually difficult to be conducted. Furthermore, the uses of this method allow failure evaluation and it forecast occurrence. Like any mechanical structure, prostheses are sensible to failures. The cyclic nature of the loading that components are exposed means that fatigue failures are the type of failure which needs more attention in these kinds of structures. Therefore, this project aims to develop a tridimensional finite element model of dental prosthesis in order to evaluate the fatigue problem. Methods: A geometric model from a single dental prosthesis compounded by an implant, an abutment screw, an abutment, a fixation's screw and a crown will be generated from Micro CT and scanning data. Then, the geometry will be exported to finite element software where a finite element model will be created. After these steps, boundaries conditions will be applied and simulations will be done. Finally, the simulation results will be analyzed. Results: The results from fatigue simulations and analysis demonstrated that abutment screw will have a finite life in most of the analyzed cases, and the fixation screw will be an infinite life. Conclusion: The results obtained illustrate the efficiency of Finite Element Method on simulating the biomechanical conditions, mainly in dental prostheses. In this study, the fatigue conditions were explored and analyzed. Finally, the knowledge about this problem could be improved.